The Department of Skill Development: A Productive Health Workforce Replicon - Ashraf, Fatema; Yusuf, Omar Faruque; Alam, AHM Shamsul; Islam, Md Aminul; Hossain, Mohammad Kamal; Biswas, Sajal (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 118-120